Development of calibrated item bank. - Abd Razak, Nordin (Universiti Sains Malaysia, 2017)
Producing a high quality of test items needs a substantial time and efforts in developing and examining each testitem. Literature suggested this limitation can be remedied with a large collection of test items along with their measurement characteristics which termed as item bank. However, a well-developed item bank is formed by a set of high quality of test items using a rigorous development and validation procedures. In achieving this, this study attempts to describe the development of Malaysian secondary school Form two Mathematics item bank; and to examine the psychometric properties of the test items which developed based on Malaysian Mathematics Curriculum Specifications.